Anaerobic endodontic mikroflora in chronic apical periodontitis (Эндодонтия Today)
PСR-analysis of 78 root canal contents was conducted in 56 patients with apical periodontitis for identification of anaerobic microflora in a chronic process and exacerbation. Nearly 100% endodontic contamination by fuzobacteria was revealed, chromogenic bacteria predominated in exacerbation of periodontitis. Fungi Candida and enterococci have been found rather seldom, with the disease being resistant to standard medicines.